Detection of Shigella by a PCR Assay Targeting the ipaH Gene Suggests Increased Prevalence of Shigellosis in Nha Trang, Vietnam - Thiem, Vu Dinh (American Society for Microbiology, 2004)
Shigella spp. are exquisitely fastidious gram-negative organisms which frequently escape detection by traditional culture methods. To get a more complete understanding of the disease burden caused by Shigella in Nha Trang, Vietnam, real-time PCR was used to detect Shigella DNA. Randomly selected rectal swab specimens from 60 Shigella culture-positive patients and 500 Shigella culture-negative patients detected by population-based surveillance of patients seeking care for diarrhea were processed by real-time PCR. The target of the primer pair is the invasion plasmid antigen H gene sequence (ipaH), carried by all four Shigella species and enteroinvasive Escherichia coli. Shigella spp. could be isolated from the rectal swabs of 547 of 19,206 (3%) patients with diarrhea. IpaH was detected in 55 of 60 (93%) Shigella culture-positive specimens, whereas it was detected in 87 of 245 (36%) culture-negative patients free of dysentery (P < 0.001). The number of PCR cycles required to detect a PCR product was highest for culture-negative, nonbloody diarrheal specimens (mean number of cycles to detection, 36.6) and was lowest for children with culture-positive, bloody diarrheal specimens (mean number of cycles, 25.3) (P < 0.001). The data from real-time PCR amplification indicate that the culture-proven prevalence of Shigella among patients with diarrhea may underestimate the prevalence of Shigella infections. The clinical presentation of shigellosis may be directly related to the bacterial load.